INTERSEKSIONALITAS DAN BENTUK KETERTINDASAN JENG YAH, TOKOH UTAMA SERIES GADIS KRETEK - Fahimatul Yusro, Binti Rohmatin (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2024)
AbstractThis article aims to analyze the form of intersectionality and oppression of female characters in the series